Economic Growth and the Environmental Degradation: the Review of the Scientific Research - Lapinskienė, Giedrė; Peleckis, Kęstutis; Peleckienė, Valentina (IJRDO - Journal of Applied Management Science, 2017)
Since the 1970s, when the Club of Rome put forth the theory of “The Limits to Growth“, the environmentalquality has been considered a new prerequisite for economic growth. The idea has passed from academic andenvironmental activists to political handling. In the academic world, the centre of this discussion was so calledthe environmental Kuznets curve, representing the relationship between various indicators of environmentaldegradation and economic growth. The environmental Kuznets curve indicates that, at the early stages ofeconomic growth, pollution increases with the growing use of resources, but when a certain level of income percapita is reached, the trend reverses so that, at a higher development stage, further economic growth leads to theimprovement of the environment. The aim of this paper is to describe the evolution of the environmentalKuznets curve, starting from its roots till nowadays, to summarise and systemise the results of empirical studiesof the relationship between the air quality indicators (due to global climate change) and economic growth. In thearticle the most influential theories of the environmental economics are described in order to highlight the strongenvironmental approach. The article may be useful for scientists and policy makers, analysing the trends of theeconomic development of the countries, and dealing with the problems of the relationship between theenvironmental indicators and economic growth.